Isotopically anomalous metabolic oxygen in marine vertebrates as physiology and atmospheric proxy. (1st July 2022) - Feng, Dingsu; Tütken, Thomas; Löffler, Niklas; Tröster, Gert; Pack, Andreas
Abstract: Triple oxygen isotope data of tooth enamel (phosphate) from 16 modern marine vertebrates (sharks, mammals) from different marine habitats are presented. Marine mammal data show a clear signature of isotopically anomalous metabolic oxygen in their bioapatite. This is related to a low flux ratio of isotopically normal drinking and food water to anomalous metabolic oxygen. Traces of anomalous metabolic oxygen are also observed in shark bioapatite. Sharks and mammals have overlapping 18 O/ 16 O ratios, but distinct 17 O signatures. Our new data suggest that triple oxygen isotopes are a valuable new tracer to assess the physiology of extant and extinct marine vertebrates and may provide a new proxy for past atmospheric CO2 mixing ratios and global primary biosphere production.